Surface Modification by Combination of Dip-Pen Nanolithography and Soft Lithography for Reduction of Bacterial Adhesion (2018)
Dip-pen nanolithography (DPN) and soft lithography are techniques suitable to modify the surface of biomaterials. Modified surfaces might play a role in modulating cells and reducing bacterial adhesion and biofilm formation. The main objective of this study was threefold: first, to create patterns at microscale on model surfaces using DPN; second, to duplicate and transfer these patterns to a real biomaterial surface using a microstamping technique; and finally, to assess bacterial adhesion to these developed patterned surfaces using the cariogenic species Streptococcus mutans. DPN was used with a polymeric adhesive to create dot patterns on model surfaces. Elastomeric polydimethylsiloxane was used to duplicate the patterns and silica sol to transfer them to the medical grade stainless steel 316L surface by microstamping. Optical microscopy and atomic force microscopy (AFM) were used to characterize the patterns. S. mutans adhesion was assessed by colony-forming units (CFUs), MTTviability assay, and scanning electron microscopy (SEM). DPN allowed creating microarrays from 1 to 5 μm in diameter on model surfaces that were successfully transferred to the stainless steel 316L surface via microstamping. A significant reduction up to one order of magnitude in bacterial adhesion to micropatterned surfaces was observed. ,e presented experimental approach may be used to create patterns at microscale on a surface and transfer them to other surfaces of interest. A reduction in bacterial adhesion to patterned surfaces might have a major impact since adhesion is a key step in biofilm formation and development of biomaterial-related infections.